Effects of GO/Al2O3 and Al2O3 Nanoparticles on Concrete Durability against High Temperature, Freeze-Thaw Cycles, and Acidic Environments - Mehdi Saliani; Amin Honarbakhsh; Rahele Zhiani; Seyed Mojtaba Movahedifar; Alireza Motavalizadehkakhky (Advances in Civil Engineering)
In this paper, the effect of GO/Al2O3 and Al2O3 synthesized nanoparticles on the durability of concrete is studied. To this end, after the synthesis of nanoparticles and confirmation of nanoparticles fabrication by SEM and FT-IR spectra, three concrete samples for each experiment related to each mix design were prepared and subjected to freeze-thaw cycles, high temperature, and acidic environment. The results show that the samples containing GO/Al2O3 nanoparticles had the least weight loss in freeze-thaw cycles as well as better resistance against acidic environment and the lowest apparent changes at high temperature compared to the samples containing nano-Al2O3 and the samples without nanoparticles. The replacement of 2 wt.% of cement with GO/Al2O3 nanoparticles results in the highest increase in concrete durability. The presence of nanoparticles in the concrete microstructure and the validation of the results are investigated by FT-IR, SEM, and EDX spectra.